Bacterium-Like Particles for Efficient Immune Stimulation of Existing Vaccines and New Subunit Vaccines in Mucosal Applications - Van Braeckel-Budimir, Natalija; Haijema, Bert Jan; Leenhouts, Kees (Frontiers in Immunology, 2013)
The successful development of a mucosal vaccine critically depends on the use of a safe and effective immunostimulant and/or carrier system. This review describes the effectiveness and mode of action of an immunostimulating particle derived from bacteria in mucosal subunit vaccines. The non-living particles, designated Bacterium-like Particles (BLPs) are based on the food-grade bacterium Lactococcus lactis. The focus of the overview is on the development of intranasal BLP-based vaccines to prevent diseases caused by influenza and respiratory syncytial virus, and includes a selection of Phase I clinical data for the intranasal FluGEM vaccine.